2000
DOI: 10.1161/01.cir.102.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Tissue Factor Pathway Inhibitor Modulates Thrombus Formation in an In Vivo Model of Rabbit Carotid Artery Stenosis and Endothelial Injury

Abstract: Background —Tissue factor pathway inhibitor (TFPI) is the sole known inhibitor of the extrinsic coagulation pathway of physiological importance; however, its role in modulating thrombosis in vivo is still unclear. Methods and Results —Intravascular thrombosis was initiated by placing an external constrictor around endothelially injured rabbit carotid arteries (n=10). Carotid blood flow velocity was measured by a Doppler flow probe. After placement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Furthermore, it has been shown that TFPI modulates thrombus formation in experimental models in vivo, 16 primarily by attenuating the procoagulant activity and overexpression of TF. 17,18 Therefore, we tested the levels of TFPI by utilizing a homemade enzyme-linked immunosorbent assay.…”
Section: Shift Of the Tf/tfpi Ratio Suggests An Increased Atherothrommentioning
confidence: 99%
“…Furthermore, it has been shown that TFPI modulates thrombus formation in experimental models in vivo, 16 primarily by attenuating the procoagulant activity and overexpression of TF. 17,18 Therefore, we tested the levels of TFPI by utilizing a homemade enzyme-linked immunosorbent assay.…”
Section: Shift Of the Tf/tfpi Ratio Suggests An Increased Atherothrommentioning
confidence: 99%
“…5 In addition, human atherosclerotic arterial segments exposed to flowing blood are less thrombogenic when treated with recombinant TFPI or a polyclonal antibody against tissue factor. 16 Conversely, inhibition of endogenous TFPI with a polyclonal antibody leads to more thrombus formation in a rabbit carotid artery injury model, 6 and a mutation in the TFPI gene, resulting in the replacement of proline at position 151 by leucine, was recently shown to be a risk factor for vascular thrombosis in humans. 17 Mice homozygous for an inactive TFPI allele generated by gene targeting exhibit an embryonic lethal phenotype that seems to be due to disseminated thrombosis.…”
Section: Westrick Et Al Tissue Factor Pathway Inhibitor In Atherosclementioning
confidence: 99%
“…Overexpression of TFPI has been shown to reduce thrombus formation after vascular injury in animal models, 4,5 whereas reduced endogenous TFPI activity may enhance thrombus formation. 6 Mice genetically engineered to be completely deficient in functional TFPI demonstrate embryonic lethality, whereas mice heterozygous for TFPI deficiency appear normal, although plasma TFPI activity is reduced. 7 To test the hypothesis that modest reductions in TFPI levels will promote atherosclerosis and thrombosis, mice with a combined apolipoprotein E (apoE) and TFPI deficiency were generated and analyzed for the development of atherosclerosis throughout the vascular tree and for thrombosis after plaque injury.…”
mentioning
confidence: 99%
“…Animal studies have demonstrated an important in vivo regulatory role of TFPI in vascular thrombosis. 10,11 Variations in TFPI expression may be particularly important in the setting of other prothrombotic risk factors. In a synthetic in vitro assay of thrombin generation, reduction of TFPI concentration by 50% resulted in a slight increase in thrombin generation.…”
mentioning
confidence: 99%